Theoretical and Methodological Basis of Income Account - Abdusaidov Sanjar Jaloliddin o’g’li (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2023)
This research paper delves into the theoretical and methodological foundations of the income account within the System of National Accounts (SNA) in the examples of Uzbekistan. It provides an in-depth analysis of the principles guiding the measurement and classification of income, and how these are applied in economic reporting. In conclusion, article provides both methodological and theoretical background of the basis of Income Account.